Starting a business all-in-one for dummies - Allen, Kathleen R. (--For dummies., 2015)
The book compilation in this volume covers entrepreneurship, business plan development, initiating an online business, franchising and home-based businesses, bookkeeping and accounting, financial management, employee management, and marketing/branding.